Patterns of Conversion in the Nominal Sentence in the Diwan of Ali Mahmoud Taha - A grammatical study (Raparin Journal of Humanities (RJH), 2024)
This study seeks to reveal the patterns and images that the nominal sentence came to in the Diwan, showing the moral effect caused by the multiplicity of patterns. The method of transcription, and the study dealt with grammatical patterns as the ancient grammarians dealt with them, not as the modern transformationalists, for the ancient grammarians referred to the deep structure not by its term, but by its concept, which is the word (origin) or (analogy).